PROBLEMS WITH CHILDREN'S UPBRINGING IN YOUNG FAMILIES - Izaitullaeva Lazokat Eshimbaevna (Web of Journals Publishing, 2023)
Families of all nationalities, peoples and peoples living in the territory of the Republic of Uzbekistan are included in the concept of "Uzbek family" and all families in terms of race, nationality, religion, social origin and material condition are considered in front of the state policy on family protection. have equal rights. One of the goals of the state policyis to providelegal guarantees for all of them to develop their own language and culture, to pass on their national traditions and values to the next generation. This article describes the development of positive qualitiesin the relationship between husband and wife and the problems that arise in the family.
Keywords: Family, legal guarantee, love, personal life, husband and wife relationship, family problems, bride’s duty, life.